Analisis Perceived Ease of Use, Perceived Security, Perceived Risk pada Pengguna Potensial Paylater di Kalangan Gen Z - Gita Safitri; Usep Suhud; Meta Bara Berutu (Teewan Journal Solutions, 2026)
This study aims to analyse the influence of perceived ease of use, perceived security, and perceived risk on user trust and intention to use a paylater service among Generation Z in Jakarta. A quantitative approach was employed using purposive sampling, and the data were analysed through Structural Equation Modelling (SEM) with the AMOS software. Primary data were collected through an online Likert-scale questionnaire with a sample of 250 respondents. The research results show that perceived ease of use has a significant positive effect on both user trust and intention to use. Furthermore, perceived security has a significant positive effect on user trust. On the other hand, perceived security has a significant effect but with a negative direction, which is inconsistent with the initial hypothesis regarding intention to use. Meanwhile, perceived risk also proves to have a significant effect but with a positive direction, contrary to the initial hypothesis regarding user trust. However, perceived risk does not show a significant effect on intention to use. Additionally, user trust also demonstrates a significant positive effect on intention to use.